Variability and repeatability of spinal manipulation force–time characteristics in thoracic spinal manipulation on a manikin. - Nyirö, Luana; Gorrell, Lindsay M.; Cecchini, Valentina; Menon, Carlo; Elgendi, Mohamed; Schweinhardt, Petra (Chiropractic & Manual Therapies, 2024)
Background: As part of multimodal therapy, spinal manipulation (SM) is a recommended and effective treatment for musculoskeletal pain. However, the underlying physiological mechanisms for pain relief are largely unknown. SM thrusts can be described and quantified using force–time characteristics (e.g. preload force, peak force, thrust speed, thrust duration, and thrust impulse). If these biomechanical parameters of SM are important for clinical outcomes, a large variability in the delivery of SM could lead to inconsistent responses and could thereby potentially mask a significant clinical effect. Our goal was to determine variability, and repeatability of thoracic spinal manipulation (SM) force–time profiles in a sample of Swiss chiropractors. Methods: All interventions were performed on a human analogue manikin. Participating chiropractors received three case scenarios with the following scenarios: 50-year-old male patient, 30-year-old male athlete, and a 70-year-old female patient, each presenting with uncomplicated musculoskeletal thoracic pain. Clinicians were asked to perform three consecutive thoracic SM thrusts for each of the scenarios and repeated the same interventions after 24–48 h. Results: Eighty-one chiropractors participated in the study, including 32 females (39.5%) with a mean age of 45.22 ± 12.96 years. The variability in SM force–time characteristics between clinicians was substantial, with preload forces ranging from 4.50 to 450.25 N and peak forces ranging from 146.08 to 1285.17 N. Significant differences between case scenarios were observed for peak force (p < 0.0001), maximum thrust speed (p = 0.0002), and thrust impulse (p = 0.0004). Except for thrust duration, repeatability within and between sessions was fair to excellent (ICCs between 0.578 and 0.957). Conclusion: Substantial variability in application of SM was evident across clinicians and between case scenarios. Despite substantial clinician-dependent variability, the high repeatability of thoracic SM thrusts suggests a level of standardization in SM delivery, indicating that chiropractors might have 'their' individual force–time profile that they are capable to reproduce. Further research based on these findings should explore how to enhance the consistency, effectiveness, and safety of thoracic SM delivered clinically to humans.